Biography as a Source and a Methodology in Humanities Research - I Nyoman Wijaya (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2019)
This study discusses whether a biography can function as a source and a methodology in the research of humanities. Taking biography as a source, researchers of humanities can use a collection of biographical facts as research material or make it as a resource of writing. While taking it as a methodology, they manage to apply biographical methodology as a science in their research. This is not a simple issue because the 1980s biographical thinking cannot adapt themselves with the latest development in the science of humanities after the emergence of post-structuralist approaches. The approach of scientific biography of 1990s cannot adapt itself either, and seems to be awkward, and difficult to be followed up. Therefore, the authority of history as a science in universities in Indonesia needs to hold a congress to seek a contemporary biographical thinking which can keep up with the influence of post-modern approach [beyond modernism] and post-structuralist theories [beyond structuralism] in the researches of humanities. This study attempts to give some preliminary thoughts by revealing the weaknesses of the previous biographical methodology and also attempts to complete it by offering some alternative thoughts through borrowing or absorbing relevant post- structuralist theories.